Roux-en-Y gastric bypass for intractable biliary reflux in an individual with incomplete tetraplegia. (July 2015) - Caruso, Deborah; Tower, Donald; Goetz, Lance
Abstract : Context: Gastroesophageal reflux disease (GERD) is a common complication in the spinal cord injury (SCI) population. Surgical treatment of GERD has a unique risk/benefit profile in this population. Findings: This 68-year-old male with chronic incomplete tetraplegia, dyslipidemia, and well-controlled diabetes mellitus underwent Roux-en-Y gastric bypass surgery (RYGBP) for intractable biliary reflux. Postoperatively, the patient had resolution of his symptoms but he also presented with significant weight loss and dumping syndrome. While he did have improvement in his dyslipidemia there was no change in his functional status. Conclusions: RYGBP is an option for refractory GERD treatment in the SCI population but preoperative risk assessment and close monitoring postoperatively is essential.